Morphological alterations in two siblings with autosomal recessive congenital ichthyosis associated with CYP4F22 mutations. (1st April 2017) - Gruber, R.; Rainer, G.; Weiss, A.; Udvardi, A.; Thiele, H.; Eckl, K.M.; Schupart, R.; Nürnberg, P.; Zschocke, J.; Schmuth, M.; Volc‐Platzer, B.; Hennies, H.C.
Summary: Autosomal recessive congenital ichthyosis (ARCI) caused by mutations in CYP4F22 is very rare. CyP4F22, a protein of the cytochrome‐P450 family 4, encodes an epidermal ω‐hydroxylase decisive in the formation of acylceramides, which is hypothesized to be crucial for skin‐barrier function. We report a girl with consanguineous parents presenting as collodion baby with contractures of the great joints and palmoplantar hyperlinearity. In the course of the disease she developed fine scaling of the skin with erythroderma, the latter disappearing until the age of 6 months. Her sister showed a generalized fine‐scaling phenotype, and, interestingly, was born without a collodion membrane. The analysis of all known candidate genes for ARCI in parallel with a next‐generation sequencing approach using a newly designed dermatogenetics gene panel revealed a previously unknown homozygous splice‐site mutation c.549+5G>C in CYP4F22 in both girls, confirming the diagnosis of ARCI. Ultrastructural analysis by transmission electron microscopy in both patients showed epidermal hyperplasia, orthohyperkeratosis with persistence of corneodesmosomes into the outer stratum corneum layers, fragmented and disorganized lamellar lipid bilayers, which could be ascribed to inhomogeneous lamellar body secretion, as well as lamellar body and lipid entombment in the corneocytes. These findings correlated with increased transepidermal water loss on the functional level. For the first time, we report a collodion baby phenotype and epidermal barrier impairment in CyP4F22‐deficient epidermis at both the ultrastructural and functional level, and corroborate the importance of CyP4F22 for epidermal maturation and barrier function.